PERAN KOMUNITAS LOKAL DALAM PENGEMBANGAN PARIWISATA DI DESA WISATA PERKEBUNAN BUKIT LAWANG KABUPATEN LANGKAТ - Suprapto, Yon (Politeknik Pariwisata Medan, 2025)
This study aims to analyze the form and level of local community participation in tourism development and identify factors that influence community involvement in Bukit Lawang Plantation Tourism Village, Langkat Regency. The method used in this research is descriptive qualitative with data collection through interviews, ohservation, and documentation. The results showed that local community participation was very significant in various aspects, such as tourism operations, homestay management, und provision of tour guide services. In addition, local communities are involved in environmental conservation that supports the sustainability of ecotourism in Bukit Lawang, especially related to the protection of Sumatran orangutans. The main factors influencing community involvement are awareness of the economic potential generated by tourism, the availability of adequate infrastructure, support from government and non-government organizations, and training provided. However, the study also found that there are still challenges in equitable distribution of tourism benefits umong community groups, mainly due to limited access to capital, technology, and education. This research is expected to contribute to the development of a more inclusive and sustainable community-based tourism stralegy, as well as encourage collaboration between local communities, government, and related institutions in enhancing the role of local communities in the tourism sector.